LncRNA29RIK in macrophages promotes LPS-mediated sensitivity to obesity - Wang, Rong; Gao, Yunhuan; Wang, Ya; Zhang, Yuan; Yang, Rongcun (Frontiers in Immunology, 2025)
Lipopolysaccharide (LPS, endotoxin) -mediated signaling of caspase-4 (human) and -11 (rodent) can induce the maturation of inflammatory cytokine IL-1β and cell pyroptosis, which is associated with the pathophysiology of many diseases such as obesity. However, the process by which LPS induces inflammation through caspase 4/11 is not fully understood. We found here that lncRNA29RIK plays a key role in LPS-mediated maturation of inflammatory cytokine IL-1β and pyroptosis of macrophages. Mechanistic ally, the binding of caspase 4/11 to LPS requires lncRNARIK to cause activation of the caspase 4/11 complex, which ultimately caused inflammation to promote sensitivity to high fat diet (HFD) -mediated obesity. Notably, lncRNA29RIK expression can be up-regulated by LPS. This lncRNA29 is highly conserved between humans and mice. Taken together, these results suggest that lncRNA29RIK determines the occurrence and progression of LPS-related diseases such as obesity.